New Convergence Definitions for Sequences of Sets - Ömer Kişi; Fatih Nuray (Abstract and Applied Analysis)
Several notions of convergence for subsets of metric space appear in the literature. In this paper, we define Wijsman  -convergence and Wijsman  -convergence for sequences of sets and establish some basic theorems. Furthermore, we introduce the concepts of Wijsman  I-Cauchy sequence and Wijsman  -Cauchy sequence and then study their certain properties.